2015
DOI: 10.1063/1.4927746
|View full text |Cite
|
Sign up to set email alerts
|

High temperature coefficient of resistance of low-temperature-grown VO2 films on TiO2-buffered SiO2/Si (100) substrates

Abstract: Articles you may be interested inEffect of conductive TiN buffer layer on the growth of stoichiometric VO2 films and the out-of-plane insulator-metal transition properties

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Vanadium oxides (V-O) have been widely studied during the last three decades [1][2][3][4][5][6][7][8][9][10][11][12], mostly due to their broad applications in catalysis and microelectronics. Vanadium is a transition metal with an elevated melting temperature and good corrosion resistance vs. different acids and alkalis at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium oxides (V-O) have been widely studied during the last three decades [1][2][3][4][5][6][7][8][9][10][11][12], mostly due to their broad applications in catalysis and microelectronics. Vanadium is a transition metal with an elevated melting temperature and good corrosion resistance vs. different acids and alkalis at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that TiO 2 buffer layers permit the fabrication of VO 2 films that show a sharp MIT on SiO 2 /Si(100) substrates at process temperatures below 670 K, which is compatible with a BEOL process. 17 By using the TiO 2 -buffer technique, we deposited V 1−x−y Cr x Nb y O 2 films on SiO 2 /Si(100) substrates to realize both large TCR values and an absence of thermal hysteresis. Figure 4 shows the ρ-T curves for the V 0.90 Cr 0.06 Nb 0.04 O 2 films on Al 2 O 3 and TiO 2 /SiO 2 /Si substrates.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously described the detailed conditions for growth of such films on Al 2 O 3 15 or TiO 2 /SiO 2 /Si substrates. 17 The film thickness was set at 70-110 nm, as confirmed by using a surface profiler. Note that there were no significant differences in the structural or electronic properties of the films within this thickness range.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the expected involvement of thermally induced metallic phases, the abruptness of the temperature-driven metal-insulator transition has been regarded as a critical parameter of the resistive switching based on the metal-insulator transition for both the thermal and nonthermal mechanisms, which directly determines the switching behavior, [24][25][26] and the resistive switching has been believed to be caused by the abrupt state change that is observed in the resistivity-temperature characteristics. In materials with the metal-insulator transition, the abruptness of the temperature-driven transition has been estimated from the temperature coefficient of resistivity (TCR) defined as |(1/ρ) (dρ/dT)|, where ρ is the resistivity and T is the temperature of the material, [27,28] and a large TCR of >100% K −1 (as a discontinuity in the resistivity-temperature curve) has been generally required for the resistivity-temperature characteristics to induce high-speed switching as Mott switching devices [14,21,[24][25][26] and sharp firing as Mott neurons. [5][6][7]15] However, to obtain a high TCR, highly controlled stoichiometry and crystallinity is essentially required for the switching material, [27][28][29][30][31] and severe restrictions have been imposed on the selection of the switching and substrate materials in the thin film fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7]15] However, to obtain a high TCR, highly controlled stoichiometry and crystallinity is essentially required for the switching material, [27][28][29][30][31] and severe restrictions have been imposed on the selection of the switching and substrate materials in the thin film fabrication. [27][28][29]31] Device applications of materials with the metalinsulator transition have therefore been complicated thus far due to the requirement of the transition abruptness.…”
Section: Introductionmentioning
confidence: 99%